Influence of emotional intelligence on sport performance in elite canoeist - Arribas-Galarraga, S.; Cecchini, J. A.; Luis-De-Cos, I.; Saies, E.; Luis-De-Cos, G. (Journal of Human Sport & Exercise, 2020)
Several studies support the hypothesis that emotions are linked with sport performance. However, only a few studies have addressed the direct relationship between emotional intelligence (EI) and sport performance. In order to address this question, emotional intelligence was assessed in 50 elite male canoeists from a total of fourteen countries. The sample was divided into two groups based on the number of medals achieved at world championships [Expert level Group 1, had won 1 - 3 medals (n = 33), and Expert level Group 2 had won more than 3 medals (n = 17)]. As a secondary goal, the influence of years of practice on sport performance was examined. Results indicate that the Level 2 expert athletes scored higher in empathy (p < .05), emotional recognition (p < .05), emotional control and regulation (p < .001) and years of practice invested in their preparation (p < .01) than the Level 1 expert athletes. These findings make a valuable contribution to answering some key questions regarding high performance sport and the role of EI in elite sport performance.